(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the issues of ensuring economic stability in industrial enterprises, especially in the textile industry, in particular, the content, essence and importance of the concept of economic stability and the factors influencing it.